MSC virtual e-abstract (ONC) - Stroke Conference 2020, Malaysia (Journal Of Cardiovascular, Neurovascular & Stroke, 2020)
Incidence rate of developing first ever stroke over a 5-year period. Post-stroke aphasia rehabilitation in Malaysia: findings from a survey with speech-language pathologists. Neuroprotective effect of nanoparticle-bounded brain-derived neurotrophic factor (bdnf) on experimental haemorrhagic stroke in rats. Adenosine a1 receptor plays role in neuroprotection by resveratrol against neurobehavioural deficits in rat model of hemorrhagic stroke.